The Development of Reference Realization and Narrative in an Australian Contact Language, Wumpurrarni English - Disbray, Samantha (Frontiers in Psychology, 2016)
The development of narrative skill has been investigated extensively in a wide range of languages, cross-linguistically and in multilingual settings (Berman & Slobin, 1994b; Hickmann, 2004; Severing & Verhoeven 2001, Strömqvist & Verhoeven, 2004). The present study investigates the development of reference realisation in narrative among Indigenous children in a remote urban township in Central Australia. The children, aged between 5 and 14 years, are speakers of a contact language, Wumpurrarni English. Language development is rarely investigated among speakers of minority languages, whose language development is often appraised in the majority language, with little attention to language performance in the speaker’s home variety. The present study addresses this gap through a fine-grained qualitative analysis of the development of reference in narrative, drawing on a complex stimulus and a model of discourse strategy. The results show a) a developmental trajectory similar to that found in other languages, with children aged eight and under producing simpler and less globally organised narratives than older speaker groups, and b) vulnerability to the changing demands of the stimulus among these younger speakers. In addition, a subset of narrations were produced in ‘school variety’, a style more like Standard Australian English, and the results for this set showed that the narrative content and global organisation of the productions by ten- and twelve–year-olds was more similar to the productions of younger children, than like-aged speakers narrating in their home variety. Analysis of speaker responses to two factors of complexity, the stimulus and code choice, illuminated mechanisms for discourse production and development, and suggest that constructing discourse requires co-ordination of an underlying schema and on-line construction of a particular story through the deployment of linguistic devices in a particular narrative context, and that these two skills are tightly interdependent, and indeed co-constructing.